Effect of mitochondrial electron transport chain inhibitors on superoxide radical generation in rat hippocampal and striatal slices - HAKLAR, GONCAGÜL (MARY ANN LIEBERT, INC, 2001)
In this study, we have compared the generation of superoxide radical in rat hippocampal and striatal slices in the presence of specific mitochondrial electron transport chain (ETC) inhibitors (complexes I and III) under control and depolarization conditions [incubation in artificial cerebrospinal fluid (ACSF) or depolarizing ACSF (dACSF), respectively]. Superoxide radical generation was increased in both ACSF- and dACSF-incubated hippocampal and striatal slices when rotenone and antimycin A were added to the incubation medium. The increase in superoxide radical was dependent on the concentration of ETC inhibitors under control, but not depolarization conditions. Rotenone was found to be more effective than antimycin A in producing superoxide radical from hippocampal and striatal slices. Our results also showed that hippocampal slices were more sensitive to ETC inhibitors compared with striatal slices. Thus, different regions of the brain seem to differ in their capacity to generate free radicals and vulnerability to oxidative stress conditions. This difference should be considered in developing therapeutic modalities against oxidative stress-related disorders and neurodegeneration.
Keywords: ALZHEIMERS-DISEASE BRAIN; OXIDATIVE STRESS; RUTHENIUM RED; NEURODEGENERATIVE DISEASES; GLUTAMATE NEUROTOXICITY; HUNTINGTONS-DISEASE; PARKINSONS-DISEASE; NERVOUS-SYSTEM; INVOLVEMENT; NEURONS